Sistem Informasi Akuntansi dan Point of Sales Perusahaan Besi UD. ABC Berbasis Website - Bobby Alexandro Arifianto; Silvia Rostianingsih; Rudy Adipranata (Jurnal Infra, 2018)
UD. ABC was a iron distributor and retail store. UD. ABC sells many type of products as steel bar, iron box, iron pipes, and aluminium expansion. However, UD. ABC currently still using the system for recording purchases and sales manually.Seeing their information system related the problems faced by UD. ABC, so accounting information system software was made to help improve business process control in UD. ABC. This accounting information system comprise computerized system of purchase, sales, profit and loss calculations, balance sheet, and display the necessary reports for company. This application uses the programming language CodeIgniter Framework and MySQL.